Design, Overdesign and Epistemic Community: A Discussion on the Limits of the Professional Field - Vargas Callegari, Rodrigo; Rodríguez Torrent, Juan Carlos; Arias Noa, Priscila (Base Diseño e Innovación, 2018)
Design, in a broad sense, is defined as a field of action of prefiguration of artificiality, through projects for the serial production of objects, artifacts, services, communication devices or more complex systems. In today's society, organized and structured through specialized work, objects become consumer goods that activate the dynamics of the market, where they are acquired by individuals to respond to functional needs, but also, through them, material culture is formed and modes of social interaction are determined. Based on the latter, the profession of design because of its contributions to industry, the economy and culture, becomes a political act in itself; this article, however, argues that: design seen only as an accelerator of the market, decreases its chances of advancing towards a professionalization of the practice and formation of a disciplinary community.